Amylolitic microbes of nira and laru from Timor Island, East Nusa Tenggara - ELIDAR NAIOLA (Biodiversitas Journal of Biological Diversity, 2008)
Thirty nine isolates of microorganisms were isolated from the nira (palm sap from inflorescence stalk of Corypha utan Lamk. or Borassus flabellifer L., laru (fermented palm sap) and their ability to produce amylase has been done. The result of screening showed that eight isolates were positive in the starch iodine test, but their amylolitic activities relatively lower. The amylolitic activities show that laru is not potential source of microbial amylases. In liquid media containing 2% soluble starch, three isolates of fungi (LG4, LMS1, and MI-1) produceamylase and reached a maximum activity at 3 days fermentation, with levels 56.31x102 , 46.78x102 and 41.49x102 U/mL (one unit activity is define as micromoles of glucose produce per mL per minute). Two yeast isolates which isolated from laru or kayu laru were showed their ability to ferment the gula aer and produce ethanol, CO2 and some organic acids, it were identified as Pichia anomala. The other bacterial isolates were identified as Bacillus licheniformis BL43, Chromobacterium sp., Lactobacillus sp., Micrococcus roseus (Staphylococcus roseus), and Bacillus coagulans, its show the lower amylase activities.Â© 2008 Jurusan Biologi FMIPA UNS Surakarta.Key words: palm sap (nira), fermented palm sap (laru), amylase, fermentation, East Nusa Tenggara